Identification of transition factors in myotube formation from proteome and transcriptome analyses - Qi ZHENG; Rong-cui HU; Cui-yun ZHU; Jing JING; Meng-yu LOU; Si-huan ZHANG; Shuang LI; Hong-guo CAO; Xiao-rong ZHANG; Ying-hui LING (Journal of Integrative Agriculture)
Muscle fibers are the main component of skeletal muscle and undergo maturation through the formation of myotubes. During early development, a population of skeletal muscle satellite cells (SSCs) proliferate into myoblasts. The myoblasts then undergo further differentiation and fusion events, leading to the development of myotubes. However, the mechanisms involved in the transition from SSCs to myotube formation remain unclear. In this study, we characterized changes in the proteomic and transcriptomic expression profiles of SSCs, myoblasts (differentiation for 2 d) and myotubes (differentiation for 10 d). Proteomic analysis identified SLMAP and STOM as potentially associated with myotube formation. In addition, some different changes in MyoD, MyoG, Myosin7 and Desmin occurred after silencing SLMAP and STOM, suggesting that they may affect changes in the myogenic marker. GO analysis indicated that the differentiation and migration factors SVIL, ENSCHIG00000026624 (AQP1) and SERPINE1 enhanced the transition from SSCs to myoblasts, accompanied by changes in the apoptotic balance. In the myoblast vs. myotube group, candidates related to cell adhesion and signal transduction were highly expressed in the myotubes. Additionally, CCN2, TGFB1, MYL2 and MYL4 were identified as hub-candidates in this group. These data enhance our existing understanding of myotube formation during early development and repair.